THE ROLE OF MUI OF NORTH SUMATRA AND BPJPH OF THE MINISTRY OF RELIGIOUS AFFAIRS IN MONITORING PRODUCT HALAL STANDARDS CHALLENGES AND STRATEGIES IN CONSUMER PROTECTION - Bambang Fitrianto; Aulia Rahman Hakim Hasibuan; Harun Firman Kurniansyah (PT. Sinergi Legal Publisher, 2024)
In the era of globalization, the demand for halal products is increasing, especially in Indonesia, which has the largest Muslim population in the world. The Indonesian Ulema Council (MUI) of North Sumatra and the Halal Product Assurance Agency (BPJPH) of the Ministry of Religious Affairs play an important role in ensuring that products in circulation meet the established halal standards. This study analyzes the challenges faced by both institutions in overseeing halal standards, including complex coordination and supervision issues. Using a normative-sociological approach, data were collected through literature studies and analyzed qualitatively. The results of the study indicate that regulatory harmonization, information technology development, and public education are the main strategies implemented to strengthen the halal product assurance system. In addition, strict law enforcement is also identified as a key factor in protecting consumers from products that do not meet halal standards. This study emphasizes the importance of cross-institutional cooperation and technological innovation to ensure justice and legal certainty in protecting Muslim consumers in Indonesia.